PS-82 GENDER FEATURES OF THE RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM (RAAS) IN PATIENTS WITH ARTERIAL HYPERTENSION IN UZBEKISTAN. (September 2016) - Umarov, Azamatjon; Vakhabova, Nargiza; Prokhorova, Anna; Narzikulova, Madina
Abstract : Objective: To study the relationship status of the renin-angiotensin-aldosterone system (RAAS) with the level of female hormones and markers of target organ damage in arterial hypertension (AH). Design and method: The study involved 20 men and 39 women with hypertension of 1–3 degrees. All women were postmenopausal. There were performed a dynamic renal angioscintigraphy and echocardiography, and determined the level of plasma renin activity (PRA), aldosterone, estradiol, 17-hydroxyprogesterone by radioimmunoassay. Results: Women registered a significantly higher concentration of aldosterone than men: 212, 5 ± 123, 9 pg / mL and 148.9 ± 82, 5 pg / m, respectively (p = 0.03). Women have found a negative relationship between the concentrations of aldosterone and estradiol levels (r = -0.3; p = 0.04) and 17-hydroxyprogesterone (r = −0.318; p = 0.04), as well as the positive relationship between aldosterone concentration and PRA (r = 0.555; p = 0.04). In addition, women have a correlation between the concentrations of female sex hormones, aldosterone and renal blood flow, glomerular filtration rate, an index of left ventricular mass (LVMI). In men, the data correlation is not established. Conclusions: Hypertensive patients revealed gender differences RAAS state with a higher concentration of aldosterone in postmenopausal women. Also, women with hypertension revealed a relationship between PRA, aldosterone levels, sex hormones and indicators of renal hemodynamics and LVMI.